Prinsip Kesantunan Berbahasa Dalam Komunikasi Siswa di Sekolah - Muhammad Farid Zulkarnain; Hilalludin Hilalludin; Adi Haironi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the principles of politeness in language as crucial guidelines in social interaction. Using a literature review method, the research elucidates six maxims of politeness: wisdom, generosity, respect, humility, agreement, and sympathy. The findings illustrate how applying these principles can enhance communication effectiveness and harmony. The implications of this research strengthen understanding of communication dynamics and social behavior, providing a theoretical foundation for developing improved interaction strategies across various cultural contexts. The study also underscores the importance of communication as a complex process facilitating mutual understanding and social adaptation. Thus, a profound understanding of politeness in language has the potential to enhance the quality of interpersonal communication and strengthen social harmony in society.